The Effect of Gossiping Group Activities Toward Fluency in Speaking at the 10th Grade Of MAN 3 Agam - Alfina, Alfina; Eliza, Eliza; Roza, Veni; Melani, Melyann (Pusdikra-Publishing.com, 2024)
This research was motivated by the findings of the researcher during observations and interviews at the 10th grade of MAN 3 Agam. Researcher found that students often used pause fillers such as